Providing a Governance Model for Information Technology (COBIT) in the Enterprise Architecture of Iran Public Libraries Foundation - Solmaz Derogar Kalkhoran; Fahimeh Babalhavaeji; Najla Hariri; Afsaneh Mozafari (International Journal of Information Science and Management, 2025)
The current study investigates using the COBIT (Control Objectives for Information and Related Technologies) framework in the enterprise architecture of the Iran Public Libraries Foundation. COBIS serves as a comprehensive framework for the management and governance of IT. COBIT helps organizations improve IT performance and realize their strategic goals, and the Enterprise Architecture (EA) is a strategic approach to align organizational components with strategic goals. Analysis, planning, design, and implementation help organizations optimize their structure and operations to achieve present and future objectives efficiently, driving digital transformation: three methodologies- eta-synthesis, Delphi, and analytical-exploratory surveys- are employed in this applied study. Using Delphi, a researcher-constructed questionnaire was given to 20 selected professionals in two stages. This resulted in the selection of 90 categories for the questionnaire construction. Accordingly, the questionnaire validity was evaluated, and the final version, including 48 items, had a content validity index above 0.79 and a content validity ratio over 0.62. Cronbach's Alpha Coefficient, which was employed to determine the reliability, proved to be 0.758. Cluster sampling was implemented in five provincial stages to guarantee sample variety from 1,836 professionals and librarians. 241 out of 638 librarians working at the main libraries were chosen randomly based on Cochran's technique. Out of them, 240 participants answered the questionnaire. The results demonstrated that the relational dimension (0.93), process dimension (0.95), and structural dimension (0.94) all had correlation coefficients for IT governance in business design. Professionals ranked business, information, technology, and applications according to their influence on organizational levels, revealing notable variations among the elements of each dimension. In summary, the success of the structural equation model of IT governance in enterprise architecture in improving organizational performance is confirmed by its robustness and strong fit.